2021
DOI: 10.1111/ene.14769
|View full text |Cite
|
Sign up to set email alerts
|

Gender differences in post‐stroke functional outcome at discharge from an intensive rehabilitation hospital

Abstract: Background: Gender differences in stroke functional recovery after rehabilitation are poorly investigated. Our aim was to compare functional outcomes at discharge from an intensive rehabilitation hospital after stroke in men and women, and to analyze their prognostic factors. Methods: Retrospective observational study of consecutive stroke patients discharged from an intensive neurological rehabilitation hospital, from January 2018 to June 2019. Modified Rankin Scale (mRS) at discharge was the main outcome mea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 16 publications
0
5
0
1
Order By: Relevance
“…After a stroke, sex was associated with lower post-stroke physical activity [32] and different improvements in physical function following home-based rehabilitation among home-dwelling patients [33]. So far, even though differences in functional outcomes after inpatient rehabilitation have been found between sexes [34,35], no evidence is available on high-intensity gait rehabilitation after suffering a stroke. A randomised trial comparing robot-assisted gait training (RAGT) versus conventional training in a population of neurologic patients, including stroke survivors, showed that walking recovery in the RAGT group was significantly improved among females compared with males [36].…”
Section: Introductionmentioning
confidence: 99%
“…After a stroke, sex was associated with lower post-stroke physical activity [32] and different improvements in physical function following home-based rehabilitation among home-dwelling patients [33]. So far, even though differences in functional outcomes after inpatient rehabilitation have been found between sexes [34,35], no evidence is available on high-intensity gait rehabilitation after suffering a stroke. A randomised trial comparing robot-assisted gait training (RAGT) versus conventional training in a population of neurologic patients, including stroke survivors, showed that walking recovery in the RAGT group was significantly improved among females compared with males [36].…”
Section: Introductionmentioning
confidence: 99%
“…In reference to the level of independence, a significant negative correlation is also shown with the age variable, where an increase in age determines a worse general functional capacity and a lower level of independence. Poggesi et al [48] found in their results that age may also be an influential factor in the patient's functional outcomes after a stroke, although it appeared to be associated with sex, so that men's functional recovery decreased with increasing age while older women continued to improve regardless of the initial deficit. Previous studies also found that age, gender and type of stroke predict long-term functional outcome after discharge [21,38].…”
Section: Discussionmentioning
confidence: 96%
“…König et al [ 32 ] claimed that age, together with the National Institutes of Health Stroke Scale score, is sufficient to correctly predict survival and functional recovery after 3 months. However, the predicting value of age on stroke rehabilitation continues to be controversial [ 33 ]. Our path analysis demonstrated that younger patients are, independently of an initial impairment, associated with better recovery, as measured by FM-UE and Barthel index measurements post-intervention.…”
Section: Discussionmentioning
confidence: 99%